Analisa Semiotik Denotasi, Konotasi dan Mitos Iklan Indomie Versi 45th Anniversary di Televisi - Andriyanto Andriyanto (Universitas Tarumanagara, 2022)
This research aims to explain the meaning of denotation, connotation and myth contained in Indomie instant noodle ads version